2014
DOI: 10.1007/s10943-014-9931-2
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Health and Confidentiality: An Exploratory Review of the Role of Chaplains

Lindsay B. Carey,
Mark A. Willis,
Lillian Krikheli
et al.

Abstract: Chaplaincy has traditionally been considered a profession highly respectful of confidentiality. Nevertheless, given increasing professional collaboration within health and welfare contexts, plus the requirements of intervention reporting and the ease of technological data sharing, it is possible that confidentiality may be sacrificed for the sake of expediency. This exploratory review considers the literature relating to the role of chaplaincy and confidentiality that suggests a number of principles which shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Military chaplains are uniquely appointed within their respective defense force to provide confidential counseling services sailors, soldiers and airmen/airwomen, ensuring personnel can wholeheartedly trust their chaplains in what they discuss with them without fear of reporting, reprimand or reprisal (48). For example, in the United States military, “Rule 503: Communication to Clergy,” states “a communication is ‘confidential’ if made to a clergyman in the clergyman's capacity as a spiritual adviser or to a clergyman's assistant in the assistant's official capacity and is not intended to be disclosed to third persons” [(49), p. III-24].…”
Section: Pastoral Narrative Disclosurementioning
confidence: 99%
“…Military chaplains are uniquely appointed within their respective defense force to provide confidential counseling services sailors, soldiers and airmen/airwomen, ensuring personnel can wholeheartedly trust their chaplains in what they discuss with them without fear of reporting, reprimand or reprisal (48). For example, in the United States military, “Rule 503: Communication to Clergy,” states “a communication is ‘confidential’ if made to a clergyman in the clergyman's capacity as a spiritual adviser or to a clergyman's assistant in the assistant's official capacity and is not intended to be disclosed to third persons” [(49), p. III-24].…”
Section: Pastoral Narrative Disclosurementioning
confidence: 99%
“…Nevertheless, amongst the nation’s doctors, there has been a strong historic tradition of Christian belief (Franklin 2018 ; Irvine 2015 ) and an increasing religious diversity (Henning et al 2015 ). There is a rigourous understanding of the contemporary issues facing chaplaincy (Carey et al 2015 , 2014 ; Carey and Cohen 2015 ; Carey 2012 ), which in contexts such as the New Zealand Defence Force (Hill et al 2016 ) needs to carefully craft pastoral care for a spiritually diverse constituency. Studies of the relationships between religion and health in New Zealand have found weak correlations between religion, spirituality, and well-being (Zhang 2020 ; Hoverd and Sibley 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Established chaplain researchers have emphasized the need for more research in this space and the importance of incorporating spiritual care as part of an holistic model of health care (Carey & Cohen, 2015;Carey et al, 2016;Stallinga, 2013;World Health Organisation, 1946). Furthermore, there is greater need to understand how chaplains work individually and as part of a team (Carey & Rumbold, 2015;Carey, Willis, Krikheli, & O'Brien, 2015;Cunningham, Panda, Lambert, Daniel, & Demars, 2017). The aim of this scoping review was to map the available literature on staff perceptions of the role and value of chaplains in first responder and military settings.…”
Section: Introductionmentioning
confidence: 99%